Self or nonself: end of a dogma? - Marie Duhamel; Michel Salzet; Michel Salzet (Frontiers in Immunology)
Immunologists generally view the notion of self and non-self as part of a broader, more contextual understanding of immune function, rather than a rigid dogma. While the classical paradigm that the primary role of the immune system is to recognize and eliminate anything foreign once provided a unifying basis for explaining tolerance and rejection, numerous discoveries have focused attention on how immune responses are finely tuned by a range of contextual cues, including tissue signals, hygienist theory, molecular mimicry, symbiotic microbes, metabolic factors and epigenetic modifications. Maternal-fetal tolerance and the persistence of microchimeric cells in adults demonstrate that genetically foreign cells can be actively integrated into the host, challenging the simple assumption that ‘foreign’ equals unconditional attack. Similarly, research into the microbiome, the virome and the phenomenon of trained innate immunity has shown that there can be beneficial or even essential relationships between the body and what has traditionally been labelled ‘non-self’. Over the last decade, the idea that the immune system strictly enforces a binary distinction has instead evolved towards a model in which it continuously interprets signals of damage or perturbation, manages complex ecological relationships with commensal or latent organisms, and recalibrates according to the organism’s life stage and environment. There remains a recognition that clonal deletion and negative selection in the thymus, together with MHC-bound peptide recognition, still underlie many core processes, and in certain clinical contexts, such as acute transplant rejection or the prevention of autoimmunity, an approximate self-non-self-categorization is directly relevant. Overall, however, the field recognizes that ‘self’ is not a static attribute defined once and for all, but rather a dynamic and context-dependent state that continues to be shaped by microbial symbioses, epigenetic reprogramming and immunoregulatory networks throughout an individual’s lifespan.